Studi Pencahayaan dan Warna di Kamar Asrama Haji dan Dampaknya Terhadap Kesejahteraan Subjektif Pengunjung - Putri Ahmadina; Mahendra Wardhana (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2025)
Lighting and color are essential elements of interior design that significantly influence occupants' comfort, mood, and overall subjective well-being. Hajj dormitories, which serve as temporary accommodations for pilgrims and visitors, often face challenges related to inadequate lighting and color schemes that do not support comfort. These conditions may negatively impact user experience and reduce the overall quality of the living environment. This study aims to analyze the effects of lighting and color in Hajj dormitory rooms on the subjective well-being of occupants. Through observation and systematic analysis, the research identifies how lighting and color schemes influence users' psychological responses. The findings indicate that dim or non-adjustable lighting can reduce both comfort and functionality, while overly striking or monotonous color schemes may create an environment that is less conducive to emotional balance. As a recommendation, this study suggests implementing adaptive lighting systems that can be adjusted according to user needs and selecting more harmonious and calming color schemes to foster a more comfortable atmosphere. By applying the principles of Positive Design, Hajj dormitory interiors can be optimized to better support the physical and psychological well-being of occupants. These findings can also serve as a reference for designing other communal spaces to enhance overall user comfort and experience.